Influence of Organic‐Cation Defects on Optoelectronic Properties of ASnI3 Perovskites A=HC(NH2)2, CH3NH3. Issue 18 (22nd March 2023) - Ji, Qun; Wu, Yilei; Gao, Xinying; Zhang, Tingbo; Zhou, Yipeng; Zhang, Yehui; Ju, Ming‐Gang; Wang, Jinlan; Zeng, Xiao Cheng
Abstract: Tin organic–inorganic halide perovskites (tin OIHPs) possess a desirable band gap and their power conversion efficiency (PCE) has reached 14 %. A commonly held view is that the organic cations in tin OIHPs would have little impact on the optoelectronic properties. Herein, we show that the defective organic cations with randomly dynamic characteristics can have marked effect on optoelectronic properties of the tin OIHPs. Hydrogen vacancies originated from the proton dissociation from FA [HC(NH2 )2 ] in FASnI3 can induce deep transition levels in the band gap but yield relatively small nonradiative recombination coefficients of 10 −15  cm 3  s −1, whereas those from MA (CH3 NH3 ) in MASnI3 can yield much larger nonradiative recombination coefficients of 10 −11  cm 3  s −1 . Additional insight into the "defect tolerance" is gained by disentangling the correlations between dynamic rotation of organic cations and charge‐carrier dynamics. Abstract : To achieve higher power conversion efficiency for tin organic–inorganic halide perovskites the critical role of organic defects in nonradiative recombination should be better understood. Random rotation of organic cation can suppress nonradiative carrier trapping owing to organic defects in FASnI3 [FA=HC(NH2 )2 ], rendering the organic contributions for defect tolerance. In contrast, organic defects in MASnI3 (MA=CH3 NH3 ) are strong and active trapping centers.